Application of discourse analysis theory to the teaching of writing to students at International Standard Programme-ULIS-VNU - Vũ, Thùy Linh (University of Languages and International Studies, 2017)
Chapter 1 provides the background on the study, including the definitions and the features of some determinant terms such as writing, discourse analysis, coherence and cohesion. Also presented in this chapter is a brief review of some previous studies on cohesion and coherence problems in EFL students’ writing. Chapter 2 demonstrates the research methods applied in the study with details on how and why these methods were implemented. Besides, the data collection procedure and data analysis methods are also illustrated in this chapter. Chapter 3, data analysis presents the results and discussion in terms of how much they answer the research questions.